2021
DOI: 10.1186/s13256-021-03097-6
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis as an immune-related adverse event following treatment with ipilimumab and nivolumab combination therapy for metastatic renal cell carcinoma: a case report

Abstract: Background Immune checkpoint inhibitors are new immunotherapy drugs globally used for many malignancies, including renal cell carcinoma. Myocarditis as an immune-related adverse event is rare but highly fatal, suggesting that its frequency may be higher than reported. This paper describes a case of myocarditis that developed asymptomatically following ipilimumab and nivolumab combination therapy for renal cell carcinoma. Case presentation A 71-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thus, it appears that a combination of multiple drugs can promote overall survival, suggesting that when the effects of methylprednisolone treatment alone are unsatisfactory, outcomes are improved by adding other immunosuppressive agents. Furthermore, six patients were treated initially with prednisone, followed by other immunosuppressive agents; three (50%) were alive after immunosuppressive therapy ( Nasr et al, 2018 ; Yamaguchi et al, 2018 ; Agrawal et al, 2019 ) and two patients were alive after receiving prednisone alone ( Guo et al, 2020 ; Miyauchi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that a combination of multiple drugs can promote overall survival, suggesting that when the effects of methylprednisolone treatment alone are unsatisfactory, outcomes are improved by adding other immunosuppressive agents. Furthermore, six patients were treated initially with prednisone, followed by other immunosuppressive agents; three (50%) were alive after immunosuppressive therapy ( Nasr et al, 2018 ; Yamaguchi et al, 2018 ; Agrawal et al, 2019 ) and two patients were alive after receiving prednisone alone ( Guo et al, 2020 ; Miyauchi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone combined with another immunosuppressive agent usually provides benefit in patients with cancer ( Nasr et al, 2018 ; Yamaguchi et al, 2018 ; Agrawal et al, 2019 ; Guo et al, 2020 ; von Itzstein et al, 2020 ; Luo et al, 2021 ), although some patients do not survive ( Konstantina et al, 2019 ). Furthermore, one case report showed that prednisone alone improved cardiac function in a patient with ICI-induced myocarditis ( Miyauchi et al, 2021 ).…”
Section: Clinical Evaluations Of Therapy Against Ici-induced Cardioto...mentioning
confidence: 99%
“…Grade 3 or higher adverse effects are seen in 7-13% of total patients treated with PD-1 inhibitors [21]. Serious side effects associated with PD-1 inhibitors include myocarditis, pneumonitis, autoimmune hepatitis, encephalitis, and hypothyroidism [1,[21][22][23][24][25]. PD-L1 assay, though FDA approved, has reduced sensitivity and specificity compared with other diagnostic assays and has limited utility in predicting the clinical benefits of ICI [26].…”
Section: Discussionmentioning
confidence: 99%
“…One such case was reported after a 70year-old Japanese female with advanced hepatocellular cancer was initiated on atezolizumab plus bevacizumab therapy [8]. Another case was reported when a 71-year-old Asian man with metastatic renal cell cancer on ipilimumab and nivolumab combination therapy presented with symptoms of rapidly worsening cardiogenic shock [9]. Similarly, it has also been reported in a 51-year-old woman with triplenegative breast cancer with a history of modified radical mastectomy after she received chemotherapy combined with PD-1 inhibitors [10].…”
Section: Adverse Eventsmentioning
confidence: 99%